Adhesive bonding : science, technology and applications - Adams, Robert D. (Woodhead Publishing, 2021)
"Adhesive Bonding: Science, Technology and Applications, Second Edition guides the reader through the fundamentals, mechanical properties and applications of adhesive bonding. This thoroughly revised and expanded new edition reflects the many advances that have occurred in recent years. Sections cover the fundamentals of adhesive bonding, explaining how adhesives and sealants work, and how to assess and treat surfaces, how adhesives perform under stress and the factors affecting fatigue and failure, stress analysis, environmental durability, non-destructive testing, impact behavior, fracture mechanics, fatigue, vibration damping, and applications in construction, automotive, marine, footwear, electrical engineering, aerospace, repair, electronics, biomedicine, and bonding of composites."--Publisher.
Previous edition: 2005.
Keywords: Adhesives.; elektronické knihy; electronic books